1975
DOI: 10.2307/368025
|View full text |Cite
|
Sign up to set email alerts
|

The Progressive Educator, Race and Ethnicity in the Depression Years: An Overview

Abstract: Few historians have analyzed the attitudes of major white progressive educators on race and ethnicity. Very little is known about what they did in the area of race relations and the schooling of minority and ethnic groups or about efforts sponsored by the Progressive Education Association to deal with racial tension and the “place” of blacks and white ethnics in American society. Likewise, the response and contribution of blacks and ethnics to progressive education has received little attention from scholars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…One could not exist without the other. At the time, the effects of the Great Depression and political unrest overseas necessitated a broader underSummer 2000 standing of how character was inextricably linked to citizenship (Goodenow, 1975;Moreo, 1996;Tyack, et al, 1984).…”
Section: Successful Livingmentioning
confidence: 97%
“…One could not exist without the other. At the time, the effects of the Great Depression and political unrest overseas necessitated a broader underSummer 2000 standing of how character was inextricably linked to citizenship (Goodenow, 1975;Moreo, 1996;Tyack, et al, 1984).…”
Section: Successful Livingmentioning
confidence: 97%
“…In den Vereinigten Staaten kam dezidierte pädagogische Kritik an Dewey nach der Bürgerrechtsbewegung auf, in der sein geistiges Erbe  und er selbst posthum  schlicht "out" waren. So konstatierte Goodenow (1975)…”
Section: Erziehung Zur Toleranz -Ethische Aspekteunclassified
“…Prior to his 1932 Progressive Education Association address, George S. Counts, a professor at Teachers College, was best know for his sociological work studying secondary schools (Counts, 1922) and the composition of US school boards (Counts, 1927). His groundbreaking findings indicated that public schools functioned far removed from democratic ideals, selecting and sorting students for specified curricula along lines of race and class (Goodenow, 1975). Furthermore, schools tended to be dominated by elite controlled school boards who insured that they reproduced the inequitable status quo (Cremin, 1961; Tyack and Hansot, 1982).…”
Section: Dare the Schools Build A New Social Order? – George Counts And Social Reconstructionismmentioning
confidence: 99%